Which patients stop working because of rheumatoid arthritis? Results of five years' follow up in 732 patients from the Early RA Study (ERAS). Issue 4 (1st April 2002) - Young, A; Dixey, J; Kulinskaya, E; Cox, N; Davies, P; Devlin, J; Emery, P; Gough, A; James, D; Prouse, P; Williams, P; Winfield, J
Abstract : Objectives: To assess the occurrence and prognostic factors for the ability to maintain paid work in patients with rheumatoid arthritis (RA). Setting: Inception cohort of patients with RA recruited from rheumatology departments in nine NHS Hospital Trusts in England. Patients: All consecutive patients with RA of less than two years' duration, before any second line (disease modifying) drug treatment, and followed up for five years. Methods: Clinical, laboratory, and radiological assessments, and all treatments were recorded prospectively using a standardised format at presentation and yearly. Outcome measures: Changes in, and loss of paid work by five years' follow up. Results: 732 patients completed the five year follow up. 353/721 (49%) were gainfully employed at the onset of RA, 211 (60%) were still working at five years, 104 (29%) stopped because of the disease, and 31 (9%) retired for reasons other than RA. Work disability at five years was more likely in manual workers (odds ratio (OR) 2.3, 95% confidence interval (CI) 1.4 to 3.8) and worse baseline Health Assessment Questionnaire (HAQ>1.5, OR 2.26, 95% CI 1.38 to 3.7). In combination with other baseline variables (erythrocyte sedimentation rate, sex, age of onset, and radiological erosions), employment outcome was predicted in 78% using multivariate analysis. Conclusions: Nearly half of the patients with RA were in paid employment at onset, work disability was an adverse outcome for a third of these patients by five years, and manual work and high baseline HAQ were important predictors for this. These details are likely to be useful to clinicians, health professionals, and patients in order to plan medical, orthopaedic, and remedial treatments in early RA. Future disease modifying treatments could be compared with this cohort of patients who were treated with conventional second line drugs.